Co-inoculation with Streptomyces thermovulgaris and commercial microbial agents enhances the reduction of antibiotic resistance genes in cattle manure composting: driving mechanisms involving microbial communities and mobile genetic elements - Jin, Erguang; Gao, Daoyu; Zhou, Yuan; Wan, Pingmin; Chen, Jie; Gong, Ping; Li, Peng (Frontiers in Microbiology, 2025)
To investigate the mechanisms by which Streptomyces thermovulgaris a2 (Sta2) enhances the reduction of antibiotic resistance genes (ARGs) in cattle manure composting, this study compared the effects of commercial microbial inoculant (CK) and its combination with Sta2 (ST). The results showed that the ST treatment extended the thermophilic phase (≥55 °C) to 18 days (compared to 11 days with CK) and increased the removal rates of tetG, sul1, ermQ, aac(6ʹ)-Ib-cr, and intI1/intI2 (by 4.8%–48.4%), simultaneously inhibiting the enrichment of sul2 and ermX. During the thermophilic phase, ST treatment slowed the decline in the abundances of key genera (e.g., Bacillus, Thermobacillus, Brachybacterium) and effectively promoted the growth of Actinomadura and Longispora within Actinobacteria. Redundancy analysis revealed that bacterial community succession (56.3%) and mobile genetic elements (MGEs, 30.7%) were key drivers of ARG dynamics, with intI1 and Firmicutes positively regulating most ARGs. Co-occurrence network analysis identified Lysinibacillus (harboring 9 ARG-MGE associations), Luteimonas (9), Brachybacterium (8), and the pathogen Corynebacterium (6) as multidrug resistant hosts. In summary, ST treatment enhanced the reduction of certain genes and multidrug-resistant host control by prolonging the thermophilic duration, reconstructing the microbial community composition, and effectively inhibiting intI1- and intI2-mediated horizontal gene transfer.